PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA KOPERASI PEGAWAI PEMERINTAH KOTA BANDUNG (KPKB) - Kusnandar, - (2009)
This purpose of research is to know how big working capital influence to profitability. Working capital as independent variable and profitability as dependen variable. This research hypothesis is to know whether working capital have an effect on positive to profitability. Research method which applied is deskriftif analysis. Data which checked is Koperasi Pegawai Pemerintah Kota Bandung (KPKB) financial statements year 1999- 2008. Testing of statistic apply Pearson coefficient of correlation Product Moment and then calculated how big working capital influence to profitability with uses Koefisien Determinasi. From the research earnings yield obtained the value of very strong negativity correlation. This thing indicate that if happened increase of amount of working capitals hence will be followed with downdraft of profitabilities. While working capital have influence equal to 77,44%. For research hypothesis that is working capital have an effect on positive to profitability, refused.